PENGARUH PEMBIAYAAN MURABAHAH TERHADAP KEPUASAN ANGGOTA DI BMT RUKUN ABADI SUMEDANG UTARA - Neli Purwanti (STAI Sebelas April Sumedang, 2022)
Murabahah financing is one of the products that is often used by Islamic financial institutions, including at BMT Rukun Abadi Sumedang Utara, whose contract is in accordance with the principles of shari'ah which is supported by other services so that members who will do murabahah financing feel confident and feel confident. satisfied with the BMT Rukun Abadi Sumedang Utara service, but there are also members who are not satisfied after carrying out murabahah financing. Member satisfaction in murabahah financing is a target that must be met by BMT Rukun Abadi Sumedang Utara so that members can do murabahah financing again and inform others that they are satisfied with murabahah financing in BMT Rukun Abadi Sumedang Utara. The method used in this research is a quantitative method. Determination of the sample using total sampling technique, which is a sampling technique where the number of samples is equal to the population. The reason for taking total sampling is because the total population is less than 100 so that the entire population is used as the research sample. Data collection techniques in this study used questionnaires or questionnaires, interviews, and documentation. Test techniques and data analysis include validity test, reliability test, normality test, simple linear regression, with t test and coefficient of determination (r2) using SPSS version 22. The results of this study are the effect of murabahah financing on member satisfaction. The conclusion of the research results shows that the murabahah financing variable and member satisfaction have a unidirectional relationship (b=0.260), a moderate level of closeness (r=0.240), and the murabahah financing variable contributes to the member satisfaction variable by 5.8% with very low criteria, then based on the results of hypothesis testing (t test), indicating that the hypothesis (H1) is accepted, meaning that the murabahah financing variable affects member satisfaction variables